ANALISIS PENGARUH PENGANGGURAN TERBUKA DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN DI BANTEN PERIODE TAHUN 2018-2021 - Cahya Fitra Sabrina (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
Poverty is an essential economic matter that is very vital because it can reduce the welfare of people in a region. Government subsidies, gross regional domestic product (GRDP), and the human development index (IPM), unemployment are factors that can influence poverty. Poverty in Banten Province is still relatively higher than other provinces in Indonesia. This study aims to analyze how much influence open unemployment and the Human Development Index have on Poverty in Banten Province. This research is a quantitative research, and the variables used in this research are Open Unemployment and Human Development Index. The analysis used is the panel data method in the form of cross-sectional data for 8 regencies and cities in Banten Province and time series data for 2018-2021 he results of the study show that simultaneously there is influence between the stimulus variable and the human development index on poverty. Then partially the Unemployment variable has a positive and insignificant effect on the poverty variable, while the HDI variable shows insignificant results on the poverty variable.